Seasonal variation in the Canastra cheese mycobiota - Martin, José Guilherme Prado; Silva, João Marcos Maia; César, Isabel Cristina da Rocha; da Silva, Meiriele; Santana, Samara Aparecida; Veloso, Tomás Gomes Reis; Silva, Jonas Guimarães e; Ferreira, Celia Lucia de Luces Fortes; Leech, John; Cotter, Paul D. (Frontiers in Microbiology, 2023)
Canastra cheese is the most well-known artisanal cheese produced in Brazil. Although its production includes a step to remove fungi from the cheese surface, in recent years some cheesemakers have preserved the autochthonous fungi grown during ripening due to an interest in the sensory characteristics attributed to these microorganisms. In this work, the mycobiota of artisanal cheeses produced in the Canastra region was characterized based on ITS marker gene analysis. A total of 96 artisanal cheeses from 16 different farms across 9 cities were collected during two different periods (dry and wet seasons). The Canastra cheese mycobiota was significantly impacted by the season, the city of production and the farm but altitude did not affect the fungal community of the cheeses analysed. Debaryomyces prosopidis was most abundant in the majority of samples across both seasons. During the wet season, Trichosporon asahii, Kluyveromyces lactis and Fusarium solani were the next most abundant species, followed by Torulaspora delbrueckii and Acremonium citrinum. These results highlight the importance of manufacturing practices and seasonality on the fungal composition of Canastra cheeses. These insights are particularly important in light of recent new regulation in Brazil, removing previous obstacles for surface fungi to persist on cheese. These new regulations will allow new approaches to cheese production, and ultimately, novel products.